ENGARUH BESARAN KAP, FINANCIAL DISTRESS, AUDIT TENURE DISCLOSURE, DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN YANG TERDAFTAR DI SEKTOR MANUFAKTUR BURSA EFEK INDONESIA PERIODE 2012-2015) - Analdo, Try Putera Analdo Try Putera Analdo; Hasan, Amir; Ilham, Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The users of financial statements need informations as a basic of their economic decision making. Not only in judging the fairness of financial report or detecting a fraud, but also auditors have responsibility to judge the company ability to maintain company going concern. Going concern audit opinion defined as opinion state by the auditors based on their audit, concludes that substantial doubt exists with regard to the companyâs ability to continue functioning as a business entity. In this study, we attempt empirically to investigate the relationship between KAP Size, Financial Disstress, Audit Tenure, Disclosure, Prior Year Audit Opinion on receiving a going concern audit opinion of a company. The samples are selected by purposive sampling method. All manufacturing sector company listed in Indonesia stock Exchange that had going concern such as capital had decreased significantly, asset had decreased significantly, net profit was negative from 2012-2015 are used as the population. Logistic Regression is used to test the hypothesis. From the results, indicate that Financial Disstress, Disclosure, and Prior Year Audit Opinion is significantly affect on receiving of going concern audit opinion. While the others (Audit Tenure and KAP Size) are not significantly affect on receiving of going concern audit opinion of a company.Keywords : KAP size, financial disstress, audit tenure, disclosure, prior year audit opinion, going concern, manufacture